2022
DOI: 10.1039/d1ra06731a
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of graphene oxide (GO)-based nanohybrid materials with diverse compositions: an overview

Abstract: GO undergoes synergistic interaction with MO nanoparticles and the hybrid can be used as a heterogeneous catalyst for the photocatalytic degradation of dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(15 citation statements)
references
References 263 publications
(307 reference statements)
0
15
0
Order By: Relevance
“…The corresponding calculated band gap energies are 2.8 eV for 0.07 M and 2.9 eV for 0.1 M. These two values are greater than the value for bulk CuO (E g = 1.2 eV). 51 It has been shown that PVP tends to be well-adsorbed onto the surface of metal oxide nanoparticles via H-bonding with an acid-base interaction 52 (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding calculated band gap energies are 2.8 eV for 0.07 M and 2.9 eV for 0.1 M. These two values are greater than the value for bulk CuO (E g = 1.2 eV). 51 It has been shown that PVP tends to be well-adsorbed onto the surface of metal oxide nanoparticles via H-bonding with an acid-base interaction 52 (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding calculated band gap energies are 2.8 eV for 0.07 M and 2.9 eV for 0.1 M. These two values are greater than the value for bulk CuO ( E g = 1.2 eV). 51…”
Section: Resultsmentioning
confidence: 99%
“…GO contains several oxygen-rich functional groups (carboxylic acid, hydroxyl and epoxide groups), making this lamellar 2D structure hydrophilic, easily compliable to surface modifications, exhibit better permeability, and have good dispersibility in a variety of solvents [ 222 , 225 ] Due to this oxidation, GO becomes insulative, having poor thermal conductivity compared to graphene. Hydrophobicity, electrical, and thermal conductivity is partially restored by reducing GO as rGO [ 226 ]. Each of these forms of graphene is unique and has been extensively investigated for water and wastewater treatment.…”
Section: Incorporation Of Nps In Tfncs/mmmsmentioning
confidence: 99%
“…The reduced form of DPPH could be created when it is mixed with a material or a nanomaterial either metallic or graphene-based materials that can give a hydrogen atom (antioxidant) which reflect an effective role against DPPH. This was demonstrated by the removal of the characteristic violet color (Flieger et al 2021;Majumder and Gangopadhyay 2022).…”
Section: Antioxidant Studymentioning
confidence: 99%